PERBEDAAN KEMANDIRIAN SIKAP ANTARA ANAK SULUNG DAN BUNGSU: Penelitian Deskriptif Kuantitatif - Sifa Nurfauziyyah; Dadang Kurnia; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine differences in attitude independence between the eldest and youngest children in grades IV, V and VI of SDN Gunung Batu 1, West Bogor District, Bogor City. This type of research design is descriptive quantitative through a questionnaire survey research method (questionnaire) with a total of 38 statement items. The population of this study were all students in grades IV, V and VI with a sample of 110 students divided into two, namely 55 eldest children and 55 youngest children. Samples were obtained using the Sample Random Sampling technique. For the independent variable, the mean score for the independence of the eldest child was 151.44 with the acquisition of the trend test by 31 students (56.4%) and the mean score for the independence of the youngest child was 157.33 and the acquisition of the trend test by 35 students (63.6%). Based on the results of this study, it was found that Ho was accepted because tcount (-1.64) < ttable (1.98) which showed that Ha was rejected. Thus, it can be concluded that there is no difference in attitude independence between the eldest and youngest children.